UPAYA GURU AL-QURAN HADIST DALAM MENINGKATKAN HAFALAN HADIST SISWA - Ahmad Khoiri; Nur Hidayah; Alfian Eko Rahmawan (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
, This study aims to determine the efforts of Al-Qur'an Hadith teachers in improving students' Hadith memorization and to find out what factors influence and the solutions used by Al-Qur'an Hadith teachers for class VII students at MTs Muhammadiyah Jumantono Karanganyar. This study used a qualitative method, the researcher conducted direct research on class VII students at MTs Muhammadiyah Jumantono Karanganyar. Data collection was carried out by interview, observation and documentation methods. Meanwhile, in the data analysis, the writer used a qualitative descriptive technique with the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that 1) The efforts made by Al-Qur'an teachers in improving students' memorization of hadiths by using the talqin method, tikrar method and muraja'ah method. While the tools used are textbooks, LCD projectors, markers and blackboards, and speakers. 2) Supporting factors in increasing hadith memorization, namely: the influence of the environment, teachers and family. While the inhibiting factors in increasing students' memorization of hadiths are: insufficient time allocation, lack of respect for time, and frequent forgetting. While the solutions used by Al-Qur'an Hadith teachers in increasing students' memorization of hadiths are: teacher motivation attention, giving rewards, and giving reprimands. Keywords: Effort, Al-Qur'an Hadith Teacher, Memorization, Hadith